Interrelationship between preonset auroral and magnetic signatures at a geomagnetically conjugate Iceland‐Syowa pair. Issue 2 (19th February 2014) - Motoba, T.; Ohtani, S.; Kadokura, A.; Gjerloev, J.
Abstract We present the initiation and development of Pi1‐Pi2 band pulsations in concert with spatiotemporal evolution of preonset auroral arc during an isolated auroral substorm reported by Motoba et al. (2012), and their interhemispheric similarities/dissimilarities, based on the colocated optical and magnetic field measurements at a geomagnetically conjugate Iceland‐Syowa pair. At least ~7 min prior to the auroral expansion onset, the first identifiable signature of preonset arc began with a small‐scale (~30–50 km) azimuthal beading. Interestingly, the early development of the visible arc beading for ~3–4 min was not accompanied by any ground magnetic perturbation. Then the bead‐like forms in the arc evolved into brighter, larger undulations, eventually developing into the poleward expansion. Such a preonset optical sequence was almost identical at both stations. In the transition from the beads into undulations, Pi2 pulsations were first identified clearly, followed by Pi1 pulsations a few minutes later. Whereas the Pi2 onset was coincident with the initiation of progressive increase of the preonset arc luminosity, the Pi1 onset was associated with a subsequent steep increase. The Pi2 wave cycles superimposed on the magnetic negative bay were well correlated with the preonset arc luminosity time series. These results imply the potential linkage between the ground Pi1‐Pi2 signatures in the onset region and the preonset auroral arc processes. Although the Pi1‐Pi2 features were generally similar between the two hemispheres, there was also some dissimilarity in their temporal behaviors, which could reflect a small but noteworthy interhemispheric asymmetry in the overhead conjugate preonset aurora.